Hypertension in Prenatally Undernourished Young-Adult Rats Is Maintained by Tonic Reciprocal Paraventricular— Coerulear Excitatory Interactions - Hernandez-Kunstmann, A; Rios-Ramirez, M; Constandil-Cordova, L; Saez-Briones, P; Barra-Pezo, R; Cayupe-Rivas, B (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Prenatally malnourished rats develop hypertension in adulthood, in part through increased α1-adrenoceptor-mediated outflow from the paraventricular nucleus (PVN) to the sympathetic sys-tem. We studied whether both α1-adrenoceptor-mediated noradrenergic excitatory pathways from the locus coeruleus (LC) to the PVN and their reciprocal excitatory CRFergic connections contribute to prenatal undernutrition-induced hypertension. For that purpose, we microinjected either α1-adrenoceptor or CRH receptor agonists and/or antagonists in the PVN or the LC, respectively. We also determined the α1-adrenoceptor density in whole hypothalamus and the expression levels of α1A-adrenoceptor mRNA in the PVN. The results showed that: (i) agonists microinjection increased systolic blood pressure and heart rate in normotensive eutrophic rats, but not in prena-tally malnourished subjects; (ii) antagonists microinjection reduced hypertension and tachycardia in undernourished rats, but not in eutrophic controls; (iii) in undernourished animals, antagonist administration to one nuclei allowed the agonists recover full efficacy in the complementary nu-cleus, inducing hypertension and tachycardia; (iv) early undernutrition did not modify the number of α1-adrenoceptor binding sites in hypothalamus, but reduced the number of cells expressing α1A-adrenoceptor mRNA in the PVN. These results support the hypothesis that systolic pressure and heart rate are increased by tonic reciprocal paraventricular–coerulear excitatory interactions in prenatally undernourished young-adult rats. © 2021 by the authors. Licensee MDPI, Basel, Switzerland. 1.